New Visual Narratives and Storytelling on X and Instagram: Systematic Review - Peña-Acuña, Beatriz (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The aim is to explore how X and Instagram influence new visual narratives. A systematic review in WOS, Scopus, and Eric found 30 relevant articles. The results indicate that Instagram promotes fragmented visual and emotional narratives, while Twitter/X is characterised by concise textual storytelling enriched with visual elements. Digital narratives evolve through multimodal formats and artificial intelligence, redefining content creation and consumption. It is crucial to investigate how AI enhances these networks and how visual narratives affect users' identity, behaviour, and emotions in the digital environment.